Girl practicing archery - Unknown:::Creator::::::::::::
Photograph shows a girl with a rope dangling at her waist practicing archery. She has notched an arrow and pulled back her long bow aiming it at a target in the background. She is in a clearing and surrounded by forest. The location is probably the YWCA's Camp Ayun Mapu in Big Basin, California.